2004
DOI: 10.1182/blood-2004-01-0277
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab antiproliferative effect in B-lymphoma cells is associated with acid-sphingomyelinase activation in raft microdomains

Abstract: Rituximab is a chimeric human immunoglobulin G1 (IgG1) anti-CD20 monoclonal antibody with significant activity against CD20 ؉ malignant B cells. Rituximab is currently used with success in the treatment of B-cell-derived lymphoid neoplasias either alone or in combination with chemotherapy. However, the predominant mechanism by which rituximab exerts its antitumor properties in vivo remains unknown. In the present study, we demonstrate that in Daudi and RL B-lymphoma cells, rituximab (without cross-linking) use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(87 citation statements)
references
References 43 publications
7
78
2
Order By: Relevance
“…Lipid rafts are fluctuating nanoscale assemblies of sphingolipid, cholesterol, and proteins that can be stabilized to coalesce, forming platforms that function in membrane signaling and trafficking [35]. Then the interaction between the redistributed CD20 molecules and the raft membrane protein components results in the activation of the transmembrane signaling machinery [36]. Unruh et al [37] have demonstrated that the translocation and hypercrosslinking of CD20 are necessary for rituximab to activate src family kinases (SFK)-dependent signaling and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid rafts are fluctuating nanoscale assemblies of sphingolipid, cholesterol, and proteins that can be stabilized to coalesce, forming platforms that function in membrane signaling and trafficking [35]. Then the interaction between the redistributed CD20 molecules and the raft membrane protein components results in the activation of the transmembrane signaling machinery [36]. Unruh et al [37] have demonstrated that the translocation and hypercrosslinking of CD20 are necessary for rituximab to activate src family kinases (SFK)-dependent signaling and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It remains that the exact role of slow and fast pools of cholesterol (69) in raft stabilization should be taken into consideration for future studies. In addition, Abs have been described to modulate ceramide synthesis (7), together with enhanced Fas-mediated apoptosis and cell growth inhibition (7,9). Ceramide and Abs liberate Ca 2ϩ from the same intracellular pool (70).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the therapeutic Ab anti-CD20 rituximab, but also other anti-CD20 Abs, there is a correlation between the ability of these Abs to elicit CD20 translocation into Triton DRM (4) and their capacity to initiate kinase-dependent calcium mobilization, apoptosis induction (5), and complementdependent cytolysis (6) of B lymphoma cells. Rituximab also induces ceramide accumulation together with CD20 translocation into Triton DRM, leading to activation of the ceramide-triggered signaling pathway, which mediates proliferation inhibition of B lymphoma cells (7). Lipids from DRM such as ceramide or cholesterol play a major role in the modulation of apoptosis (8,9) and cell growth (7) but also influence the outcome of HIV infection (10).…”
mentioning
confidence: 99%
“…Cells were pretreated with 100 mg/ml rituximab for 30 minutes before the addition of baboon sera, as previously described. 12,25 The cultured podocytes were processed for the cell proliferation assay or immunohistochemical analysis at day 6.…”
Section: Podocyte Culturementioning
confidence: 99%